1999
DOI: 10.1083/jcb.144.6.1259
|View full text |Cite
|
Sign up to set email alerts
|

Extensive but Coordinated Reorganization of the Membrane Skeleton in Myofibers of Dystrophic (mdx) Mice

Abstract: We used immunofluorescence techniques and confocal imaging to study the organization of the membrane skeleton of skeletal muscle fibers of mdx mice, which lack dystrophin. β-Spectrin is normally found at the sarcolemma in costameres, a rectilinear array of longitudinal strands and elements overlying Z and M lines. However, in the skeletal muscle of mdx mice, β-spectrin tends to be absent from the sarcolemma over M lines and the longitudinal strands may be disrupted or missing. Other proteins of the membrane an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
85
3
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 82 publications
5
85
3
1
Order By: Relevance
“…Whatever the mechanism, our results suggest that K19 can compete with the normal binding sites for dystrophin, which would otherwise concentrate at the sarcolemma. Because previous studies have shown that the costameric distribution of dystrophin-associated proteins, including ␤-dystroglycan, is compromised when dystrophin is absent from the sarcolemma in dystrophic muscle (Williams and Bloch, 1999b), it is not surprising that the ability of ␤-dystroglycan to concentrate at costameres is altered in myofibers that overexpress K19. Dystroglycan also redistributes in the plane of the sarcolemma in other muscular dystrophies and myopathies (O'Neill et al, 2002;Reed et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Whatever the mechanism, our results suggest that K19 can compete with the normal binding sites for dystrophin, which would otherwise concentrate at the sarcolemma. Because previous studies have shown that the costameric distribution of dystrophin-associated proteins, including ␤-dystroglycan, is compromised when dystrophin is absent from the sarcolemma in dystrophic muscle (Williams and Bloch, 1999b), it is not surprising that the ability of ␤-dystroglycan to concentrate at costameres is altered in myofibers that overexpress K19. Dystroglycan also redistributes in the plane of the sarcolemma in other muscular dystrophies and myopathies (O'Neill et al, 2002;Reed et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It suggests that these vesicles, present in a subset of fibers that overexpress K19, represent a distinct membrane population that associates with membrane-cytoskeletal proteins, such as ␤-spectrin and dystrophin, but that does not contain all of the integral membrane proteins that anchor these proteins at the sarcolemma. The presence of ␤-spectrin at these structures is unlikely to be due to interactions of that molecule or its ABD with K19 directly (Figure 2, G-I), but is instead more likely linked to the ability of ␤-spectrin to associate with muscle membranes in a manner that is independent of dystrophin (Porter et al, 1992;Ehmer et al, 1997;Williams and Bloch, 1999b). Further research will be needed to establish the nature of the aggregates and vesicles induced by the overexpression of K19, the mechanism by which they form, and their relationship to structures seen in myopathies (De Bleecker et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5] Contractioninduced stresses are generated both longitudinally as well as laterally. Lateral stresses disrupt alignment of sarcomeres and orientation of the t-tubular system, which reduce muscle force generation.…”
Section: Introductionmentioning
confidence: 99%